PELAKSANAAN PENINGKATAN KESEJAHTERAAN LANSIA DI UNIT PELAYANAN SOSIAL LANSIA WENING WARDOYO UNGARAN - Pandu Tri Pramono; Puji Astuti; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
Human is a social being who needs another people to interact with. Besides that, human grows older through a process. A nation is responsible for its peoples welfare, including the abandoned senior citizens, through a social security program. Social security program is given through a service for the seniors to improve their lives to a more decent one. The objective of the study is to describe how an social improvement program for senior citizens is conducted in Unit Pelayanan Sosial Lanjut Usia (Social Service Unit for Seniors) Wening Wardoyo in Ungaran, Central Java. The house is chosen because of the social conditions in this unit is relatively easy to observe, yet troublesome and it includes sufficient information for the study.The result of the study shows that the program of social welfare improvement for the seniors has been executed well and in accordance with Pedoman Pelaksanaan Peraturan Gubernur Nomor 53 Tahnu 2013 (the manuals of Governors Regulation number 53 year 2013) about organisation and technicals of social department of Central Java Province. Primary as well as secondary needs of the seniors have been fulfilled by the officers patiently and well.In accordance with this program for seniors, the writer recommends the welfare improvement program be conducted consistently as well as the addition to officers with medical backgrounds so that the health service can be conducted in day to day basis.